Association study of genetic variants in PLA2G4A, PLCG1, LAT, SYK, and TNFRS11A genes in NSAIDs-induced urticaria and/or angioedema patients. Issue 12 (December 2015) - Ayuso, Pedro; Plaza-Serón, María del Carmen; Doña, Inmaculada; Blanca-López, Natalia; Campo, Paloma; Cornejo-García, José A.; Perkins, James R.; Torres, Maria J.; Blanca, Miguel; Canto, Gabriela
Abstract : NSAIDs-induced urticaria and/or angioedema (NIUA) is the most frequent entity of hypersensitivity reactions to NSAIDs. The underlying cause is considered to be because of a nonspecific immunological mechanism in which mast cells are key players. We studied the association of nine single nucleotide polymorphisms in five genes involved in mast cell activation ( SYK, LAT1, PLCG1, PLA2G4A, and TNFRSF11A ) in 450 NIUA patients and 500 controls. We identified several statistically significant associations when stratifying patients by symptoms: PLA2G4A rs12746200 (urticaria vs. controls, P c =0.005). PLCG1 rs2228246 (angioedema vs. controls; P c =0.044), and TNFRS11A rs1805034 (urticaria+angioedema vs. controls; P c =0.041). The frequency of haplotype PLCG1 rs753381-rs2228246 (C-G) in angioedema-NIUA patients was lower than that in controls ( P c =0.040). In addition, the haplotype frequency of TNFRS11A rs1805034-rs35211496 (C-T) was higher among urticaria-NIUA and urticaria+angioedema-NIUA patients than the controls ( P c =0.045 and 0.046). Our results shed light on the involvement of variants in genes related to non-immunological mast cell activation in NIUA. Abstract : Supplemental Digital Content is available in the text.